Effect of Mycotoxin Exposure on Stunting and Growth Impairment in Children: A Systematic Literature Review - Anisa Aula Rahma; Jekmal Malau; Ahsanal Kasasiah (Jurnal Ners, 2025)
Stunting is a critical public health concern in low- and middle-income countries (LMICs), is traditionally attributed to malnutrition and environmental factors. Emerging evidence suggests that mycotoxin exposure is a risk factor. This systematic review, conducted using PRISMA guidelines, investigates the association between mycotoxin exposure and childhood stunting/growth impairment. Twelve relevant studies (predominantly cross-sectional and prospective cohorts) are identified, focusing on children aged 0-5 years in Africa and Asia. Aflatoxins (AFB1, AFM1) and fumonisins (UFB1) are the primary mycotoxins analyzed, measured through biomarkers in biological samples (blood, urine, breast milk). Aflatoxin exposure consistently demonstrates a negative impact on child growth, as evidenced by decreasing anthropometric z-scores (LAZ, WAZ, HAZ). Additionally, it significantly increases the risk of stunting and underweight. Potential mechanisms include disruption of the IGF signaling pathway, oxidative stress, impaired protein synthesis, intestinal barrier dysfunction, and nutrient malabsorption. Fumonisins, both independently and in co-exposure with aflatoxins, are also linked to growth impairment. This review highlights the detrimental effect of mycotoxin exposure on child growth. While aflatoxin exposure appears to be a major contributor, fumonisins warrant further investigation. Elucidating the underlying molecular mechanisms and exploring interactions with other risk factors are crucial next steps. Addressing mycotoxin-related stunting necessitates a multidisciplinary approach.